Jargon Terms by E-Sport Caster in Dota 2 The International Tournament (Sastra Inggris UNPAM, 2024)
This study is entitled Jargon Terms by E-Sport Caster in Dota 2 The International Tournament. The term sociolinguistic jargon itself is the main key in this study. The method used in this study is qualitative method. In this study, the theory from Yule (2010) is used to analyze the types of jargon used and Robin Dodsworth's theory (2015) is used to analyze the meaning of the jargon used. Based on that theory there are 52 Jargon found in The International Dota 2 tournaments. Dominated by compounding jargon type with 14 data, followed by blending 13 data, coinage 9 data, acronym 6 data, clipping 4 data, derivation 3 data, borrowing 2 data, and backformation 1 data. The International Dota 2 Tournament uses 8 types of jargon from the findings in every match at The International tournament. In identifying the meaning of the jargon found with the help of forums in the official Dota 2 community by Valve the Dota 2 developer did this to help readers better understand the jargon used by casters in the Dota 2 Tournament.